A Virtual Instructional Design Improved Breaking Bad News in Obstetrics and Gynecology Residents - Elahe Rezayof; Setareh Akhavan; Leila Afshar; Marjan Ghaemi; Leyla Sahebi; Somayeh Akbari Farmad (Tehran University of Medical Sciences, 2022)
Objective: Breaking bad news to the patient is challenging, especially for the physicians and the residents, due to the lack of structured and practical training. This study aimed to design and evaluate a novel virtual instructional design for improving obstetrics and gynecology (Ob/Gyn) residents breaking bad news skills. Materials and methods: Virtual instructional design was performed based on the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) from September 2020 to July 2021 at the Department of Ob/Gyn, a referral hospital affiliated with Tehran University of Medical Sciences, Tehran. Iran. The five steps of ADDIE virtual instructional design were applied sequentially. Results: Totally 33 of the Ob/Gyn residents included in the study that 77% needed specific training. The awareness of the performance of the residents in seven areas including interview context, strategy, planning, professionalism, empathy, knowledge, and receiving information needed to be trained for breaking bad news. The content of the virtual training package was designed based on the prior assessment needs in four multimedia lectures of professors, one short educational video, a 65-page file that combines text and images in 4 parts. The pre-test and post-test mean scores (SD) were 9.45 (2.0) and 10.67 (1.7), respectively (p-value≤0.001) in the cognitive and attitudinal domain. In the final step, the final corrections were made in the virtual training package. Interestingly, the satisfaction of residents' attitudes was 96.5%. Conclusion: Most Ob/Gyn residents do not have the necessary perception and skills to deliver bad news to the patients. Designing an appropriate virtual training package for improving communication skills is associated with satisfaction. Thus, the efficacy of the training program should be implemented for all Ob/Gyn residents.